(untitled) (Cadernos de Sociomuseologia, 2009)
Globally, the public is understood as the whole of a service’s users. In the specific case of the museums, the users are all those who make use of the service offered by the museum institution. Thus, the museum’s public corresponds not only to the visitors (people who enter or have entered the museum), but also to the part of those who, in some way, with no relationship of presence within the museum, have enjoyed the services or property made available by it (for instance the ordering of books or other material by catalogue, visit to travelling exhibitions, end users of pedagogical actions carried out in schools…) On the other hand, when we refer to the public, it is necessary to make another distinction: between the real or effective public and the potential public. The former is the group of individuals who have visited or have used the museum, while in the second case are included all the people who, due to their specific characteristics, are susceptible to become the real or effective public.